Prognostic significance of reduced handgrip strength in patients with unresectable hepatocellular carcinoma receiving HAIC combined with targeted immunotherapy - Wang, Xin-Ze; Wang, Ping; Lv, Xing; Zhang, Zi-Long; Zhang, Er-Lei; Ji, Gui-Bao (Frontiers in Immunology, 2025)
BackgroundHepatic arterial infusion chemotherapy (HAIC) combined with targeted immunotherapy has emerged as a key therapeutic option for advanced (or unresectable) hepatocellular carcinoma (HCC). Nevertheless, treatment efficacy varies significantly among individuals. Sarcopenia, characterized by loss of muscle mass and strength, may adversely affect therapeutic outcomes and patient prognosis. This study investigates the clinical relevance of sarcopenia in patients undergoing HAIC combined with targeted immunotherapy.MethodsA total of 265 patients with unresectable HCC who received HAIC combined with targeted immunotherapy were retrospectively enrolled in this study and divided into two groups (sarcopenic and non-sarcopenic group). Sarcopenia was defined based on handgrip strength (HGS), with a cutoff value of less than 28kg(male) and 18kg(female). Overall survival (OS) and progression-free survival (PFS) were compared between groups using the log-rank test and multivariate Cox proportional hazards models. Additionally, propensity score matching (PSM) was applied to minimize baseline differences and enhance comparability. Then, differences in treatment response, survival outcomes, and adverse events between the sarcopenic and non-sarcopenic groups were evaluated using appropriate statistical analyses.ResultsPatients in sarcopenia group exhibited significantly poorer OS and PFS compared to those with non-sarcopenic group. Sarcopenia was also associated with lower objective response rates. Multivariate analysis confirmed that sarcopenia was an independent prognostic factor for poor outcomes.ConclusionSarcopenia is a significant predictor of poor prognosis in patients with unresectable HCC treated with HAIC combined with targeted immunotherapy. Incorporating HGS assessment into clinical practice may help optimize individualized treatment strategies and enhance patient management.